Creating strategies and policies for equality, diversity and inclusivity within the British Society of Sports History, part one. Issue 4 (2nd October 2022) - Callan-Spenn, Amanda; Harrison, C. Keith; Jones, Tanya K.
ABSTRACT: The British Society of Sports History is actively working towards a more diverse and inclusive membership alongside the aim of encouraging a more representative research output in the field of sports history in Britain. This article provides an introduction to the process of developing and implementing strategies towards this intention. The article sits alongside and is informed by texts from authors such as Skillen and Osborne who have highlighted the continuing gender divide within sports history and the traditional leaning towards a male centred approach, and Evans et al, who have recently focussed on the disappointing legacy of the 'Black Lives Matter' movement within the field. Not limited to these particular underrepresented groups, the article considers the questions which need to be asked to produce useful and considered policies for inclusivity. With collaboration from members of the North American Society for Sport History, the author draws no conclusions, but hopes to contribute to the debate related to the inclusion of marginalised or underrepresented individuals within our sphere of academia.